(3GdeMGSHI aj bWGY GdSjGMI h GdafGOb (B/s - (3YHO GddWja, fGUQ fhQ GdOjfs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2006)
(3ENJU gPG GdcJGH HGdeMGSHI aj bWGY GdSjGMI hGdafGOb MjK bSe GdeDda GdcJGH Edi SHYI aUhd, MjK jNJU GdaUd GdChd HGdJYQja HCgejI GdeMGSHI cfXGe ddeYdheGJ, hjNJU GdaUd GdKGfj HJchjf GdTQcGJ GdSjGMjI hGdafObjI ShGA cGfJ TQcGJ JVGef Ch JhUjI HSjWI Ch TQcI eSGgeI, hjJfGhd GdeDda aj GdaUd GdKGdK eYGdLI GdCMOGK GdeGdjI GdeJQJHI Ydi eRGhdI GdfTGW aj GdefTBJ GdSjGMjI hGdafObjI, hJWQb GdeDda aj GdaUd GdQGHY Edi GdeMGSHI GdOGNdjI aj GdefTBJ GdafObjI (B((3fXGe eMGSHI GdJcGdja hfXGe GdeMGSHI GdEOGQjI(B)(3, hJfGhd GdeDda aj GdaUd GdNGeS GdeYGdLGJ GdeMGSHjI GdeJUdI HcjajI JhRjY GdCQHGM hGdNSGFQ aj GdTQcGJ GdSjGMjI hGdafObjI, ceG CSJYQV aj GdaUd GdSGOS GdeYGdLGJ GdeMGSHjI GdeJUdI HJYOjd YbO GdTQcI aj GdTQcGJ GdSjGMjI hGdafObjI, MjK jJfGhd JYOjd CSS JhRjY GdCQHGM hGdNSGFQ hRjGOI QCS eGd GdTQcGA hJNajV QCS eGd GdTQcGA, hjJfGhd RjGOI QCS GdeGd aj GdTQcGJ GdeSGgeI, hCNjQkG JfGhd GdeDda aj GdaUd GdSGHY GfbVGA GdTQcGJ GdSjGMjI hGdafObjI ef NdGd GdJUajI ShGA HGdfSHI dTQcGJ GdJVGef Ch TQcGJ GdJhUjI GdHSjWI Ch GdTQcGJ GdeSGgeI, MjK JfGhd aj gPG GdUOO cd ef GdJUajI GdahQjI hGdJUajI GdJOQjLjIs
Keywords: (3GdSjGMIs; (3GdafGObs; (3GdeMGSHIs; (3bWGY GdSjGMIs